Reconstructing Islamic Mindfulness as an Approach to Mental Health for Generation Z: A Literature Review Based on Al-Baqarah 286 - Faza Daffa Al Khirzin; Naqiyah Naqiyah; Nisrina Tuhfatul Azizah; Mohammed Elfadil Ahmed Bakhit (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2026)
This study aims to reconstruct the concept of Islamic mindfulness based on Q.S. Al-Baqarah verse 286 as an alternative approach to addressing mental health issues among Generation Z. This research employed a qualitative approach using library research with thematic interpretation and descriptive-critical analysis. Data were obtained from the Qur’an, classical and contemporary tafsir literature, psychology books, and scientific journals discussing mindfulness, Islamic psychology, and mental health. The findings revealed that Al-Baqarah verse 286 contains three major dimensions of Islamic mindfulness, namely self-awareness, self-acceptance, and emotional regulation, which were reconstructed into the 3L I-Mind model consisting of Limit, Load, and Lightness. This model emphasizes awareness of self-capacity, moral responsibility in facing life burdens, and spiritual relief through prayer and reliance on Allah. The novelty of this study lies in the reconstruction of Al-Baqarah 286 as a systematic and applicable Islamic mindfulness framework that integrates Qur’anic values with modern mental health theories. This study implies that Islamic mindfulness may serve as a contextual psycho-spiritual approach to strengthen the mental resilience of Muslim Generation Z in the digital era.